Conditions for success in introducing telemedicine in diabetes foot care: a qualitative inquiry. Issue 1 (December 2017) - Kolltveit, Beate-Christin; Gjengedal, Eva; Graue, Marit; Iversen, Marjolein; Thorne, Sally; Kirkevold, Marit
Abstract Background The uptake of various telehealth technologies to deliver health care services at a distance is expanding; however more knowledge is needed to help understand vital components for success in using telehealth in different work settings. This study was part of a larger trial designed to investigate the effect of an interactive telemedicine platform. The platform consisted of a web based ulcer record linked to a mobile phone to provide care for people with diabetic foot ulcers in outpatient clinics in specialist hospital care in collaboration with primary health care. The aim of this qualitative study was to identify perceptions of health care professionals in different working settings with respect to facilitators to engagement and participation in the application of telemedicine. Methods Ten focus groups were conducted with health care professionals and leaders in Western Norway between January 2014 and June 2015 using Interpretive Description, an applied qualitative research strategy. Results Four key conditions for success in using telemedicine as a new technology in diabetes foot care were identified: technology and training that were user-friendly; having a telemedicine champion in the work setting; the support of committed and responsible leaders; and effective communication channels at the organizational level. Conclusions Successful larger scale implementation of telemedicine must involve consideration of complex contextual and organizational factors associated with different work settings. This form of new care technology in diabetes foot care often involves health care professionals working across different settings with different management systems and organizational cultures. Therefore, attention to the distinct needs of each staff group seems an essential condition for effective implementation.